2001
DOI: 10.1016/s1097-2765(01)00324-0
|View full text |Cite
|
Sign up to set email alerts
|

Akt-Mediated Phosphorylation of the G Protein-Coupled Receptor EDG-1 Is Required for Endothelial Cell Chemotaxis

Abstract: The role of the protein kinase Akt in cell migration is incompletely understood. Here we show that sphingosine-1-phosphate (S1P)-induced endothelial cell migration requires the Akt-mediated phosphorylation of the G protein-coupled receptor (GPCR) EDG-1. Activated Akt binds to EDG-1 and phosphorylates the third intracellular loop at the T(236) residue. Transactivation of EDG-1 by Akt is not required for G(i)-dependent signaling but is indispensable for Rac activation, cortical actin assembly, and chemotaxis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
263
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(282 citation statements)
references
References 36 publications
16
263
1
2
Order By: Relevance
“…4). In the model, Rac1 activation lies downstream of Akt-mediated BLT2 phosphorylation, which is consistent with the findings that the small GTPase Rac1 plays a pivotal role in actin reorganisation, cell polarisation, and chemotactic migration [11,24]. Also in the model, Akt activation lies upstream of BLT2 phosphorylation, and indeed we found that activation of Akt itself by stimulation with LTB 4 or CAY10583 (also known as Compound A) were similar in wild-type BLT2 and the T355A mutant ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…4). In the model, Rac1 activation lies downstream of Akt-mediated BLT2 phosphorylation, which is consistent with the findings that the small GTPase Rac1 plays a pivotal role in actin reorganisation, cell polarisation, and chemotactic migration [11,24]. Also in the model, Akt activation lies upstream of BLT2 phosphorylation, and indeed we found that activation of Akt itself by stimulation with LTB 4 or CAY10583 (also known as Compound A) were similar in wild-type BLT2 and the T355A mutant ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, accumulating evidence suggests that Gbc subunits released from Ga upon stimulation of GPCRs lead to the activation of PI3K-c, and subsequently Akt [10]. The signaling mechanism by which BLT2 phosphorylation leads to Rac1 regulation has not been characterized, but it was previously reported that Akt mediates phosphorylation of sphingosine-1-phosphate receptor (EDG-1) to regulate Rac activation and subsequent chemotaxis [11]. Further, it was shown that phosphorylated EDG-1 recruites Rac exchange factor Tiam1 and Rac to cell membrane [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Akt stimulates tumor progression by promoting cell invasiveness and angiogenesis (Gallis et al, 1999;Lee et al, 2001). These observations establish Akt as an attractive target for cancer therapy (Hill and Hemmings, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, activation of PKB is induced by S1P (ligand for S1P1) [34], CCL19/CCL21 (ligands for CCR7) [34], CXCL13 (ligand for CXCR5) [34] and CXCL12 (ligand for CXCR4) [35], most probably downstream of PI3 K [34]. Interestingly, PKB dependent phosphorylation of S1P1 is required for S1P1 mediated chemotaxis [36]. Furthermore, KLF2, a key transcriptional regulator of S1P1 expression, is dynamically controlled by a well-known PKB targets, FoxO proteins [37,38].…”
Section: Immune Cell Intrinsic Role Of Pkb In Motility Activation Dmentioning
confidence: 99%